Frenulectomy with Diode Laser Technology in Paeditric Patients: Quantitative and Qualitative Evaluations. Randomized Double- Blind Clinical Trial - Gian Luca Sfasciotti; Francesca Zara; Miriam Fioravanti; Mariana Guaragna; Gaspare Palaia; Antonella Polimeni (Applied Sciences, 2020)
Background: Ankyloglossia is an anatomical alteration of the frenulum length, volume, compactness, and insertion. It can lead to alterations in the ability to swallow and chewing, and dysfunctional coordination amongst cranio-facial muscles; these alterations are often responsible for respiratory alterations, skeletal malocclusions and dyslalia or the delay of speech. The aim of this study is to estimate the efficacy of lingual frenulectomy with diode-laser technology through a qualitative and quantitative evaluation. Methods: One hundred and twenty-five pediatric patients were recruited: 100 with a lingual pathological frenulum were randomly divided into four operating groups; the other 25 with a borderline pathological frenulum were recruited as a control group. Each patient was included in a follow-up program (T0-T1-T2-T3-T4) for a quantitative and qualitative evaluation: the first through an accurate measurement of Kotlow’s free tongue measurement (≥16), Mouth Opening with Tongue Tip to incisive papilla (MOTTIP), Maximal Intercisal Mouth Opening (MIO) and Protrusion; and the second using the Assessment Tool for Lingual Frenulum Function (ATLFF), Bristol Tongue Assessment Tool (BTAT), and grade of tongue functionality. Results: The increase of the aforementioned quantitative parameters was circa 10 mm, and all patients reacquired full functionality of the tongue. Conclusions: Diode-laser technology is efficient and innovative in the treatment of pathological lingual frenulums.